2012
DOI: 10.1038/labinvest.2012.113
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B lowers portal pressure in cirrhotic rats and attenuates contraction of rat hepatic stellate cells by inhibiting RhoA signaling pathway

Abstract: The contraction of hepatic stellate cells (HSCs) has a critical role in the regulation of intrahepatic vascular resistance and portal hypertension. Previous studies have confirmed that salvianolic acid B (Sal B) is effective against liver fibrosis. In the present study, we evaluated the effect of Sal B on portal hypertension and on HSCs contractility. Liver cirrhosis was induced in rats by peritoneal injection of dimethylnitrosamine and the portal pressure was measured. HSCs contraction was evaluated by collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…Stellate cell contraction has been reported to be mediated by Ca++ dependent and independent mechanisms 6366 . Stellate cell contraction has a multitude of effects in the injured liver including in perisinuoidal constriction and portal hypertension, and may also lead to the collapse and shrunken state of cirrhotic livers 45 .…”
Section: Fibrogenesis – Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Stellate cell contraction has been reported to be mediated by Ca++ dependent and independent mechanisms 6366 . Stellate cell contraction has a multitude of effects in the injured liver including in perisinuoidal constriction and portal hypertension, and may also lead to the collapse and shrunken state of cirrhotic livers 45 .…”
Section: Fibrogenesis – Pathophysiologymentioning
confidence: 99%
“…Stellate cell contraction has a multitude of effects in the injured liver including in perisinuoidal constriction and portal hypertension, and may also lead to the collapse and shrunken state of cirrhotic livers 45 . Stellate cell contractility is likely tied to multiple different systems, including the endothelin, angiotensin, adrenergic, and perhaps other systems 44, 45, 6671 .…”
Section: Fibrogenesis – Pathophysiologymentioning
confidence: 99%
“…This inhibitory effect on RhoA/ROCK could be exerted by the effective components of QSKL. Salvianolic acid B, one of the major effective constituents identified in Salvia Miltiorrhiza Bunge, has been shown to inhibit the RhoA signaling pathway in cirrhotic rats [30]. Other components of QSKL, such as astragaloside IV, luteolin, and tanshinone IIA, have also been shown to have inhibitory effects on the RhoA/ROCK pathway under various pathological conditions [3134].…”
Section: Discussionmentioning
confidence: 99%
“…FZHYC can also promote apoptosis of activated HSCs, inhibit synthesis and secretion of collagen, inhibit angiogenesis and promote degradation of collagen [59] . Studies showed that FZHYC achieved its antifibrotic activity through multiple signal pathways and targets [57,58,[60][61][62][63] , such as transforming growth factor β-1 (TGF-β1), SMADs, insulin-like growth factors-1 (IGF-1), phosphatidylinositol 3-kinase (PI3K), extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinase (p38 MAPK), RhoA/Rho-associated coiled-coil forming protein kinase (ROCK) and renin-angiotensin system (RAS) signaling pathways [64,65] .…”
Section: Mechanisms Of Tcm In Treatment Of Liver Diseases Are Studiedmentioning
confidence: 99%